Identification of Orangutan Nest Tree Types (Pongo pygmaeus) in KHDTK Mungku Baru, Palangka Raya, Central Kalimantan: IDENTIFIKASI JENIS POHON SARANG ORANGUTAN (Pongo Pygmaeus) DI KHDTK MUNGKU BARU, PALANGKA RAYA, KALIMANTAN TENGAH - Ardiyansyah Purnama; Mariaty Mariaty; Armadiyanto Armadiyanto (Jurusan Kehutanan -FHIL-UHO, 2024)
Muhammadiyah University of Palangkaraya has a KHDTK covering an area of ​​4,910 ha. However, research on Orangutan is still very minimal and limited to KHDTK Mungku Baru. Therefore, this research aims to determine several trees used for habitat and food for orangutans (Pongo pygmaeus) in KHDTK Mungku Baru, Palangka Raya City, Central Kalimantan. Observations from research on Orangutan (P. pygmaeus) nests showed that there were 19 nests from 27 tree species identified in 9 different tree species, dominated by Meranti (Shorea) and Guava (Syszgium) trees. Characteristics of Orangutan (P. pygmaeus) nests: There are 5 types of nests, namely types A, B, C, D and E.